(untitled) (El-Wahat Journal for Research and Studies, 2021)
This Is An Indication Of The Value And Importance Of Speech. In The Present Era, I Have Written Theories And Philosophies That Establish And Analyze The Discourse, Taking Into Consideration The Sender And The Sender. Mechanism . There Is No Doubt That This Arab Speech Is Composed Of Clear Words, And Other Than The Different Dialects, But It Has The Support Of Arab Heritage Sources And Codes. From Which We Can Ask A Question: Is There In Our Local Dialect What Applies To What Has Been Mentioned Previously, What Supports Or Strengthens In The Books Of The Stranger And The Koranic Interpretation? Key Words- 1 Algerian Vernacular 2, Qur’anic Interpretation 3, Dialect 4, Djelfa Region, 5 Compatibility Positions